MENGUNGKAP ESENSI BAURAN PEMASARAN SYARIAH: KAJIAN EKSPLORASI STRATEGI BANK SYARIAH INDONESIA - Yorina Putri; Muhammad Iqbal Fasa; Is Susanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research reveals the essence of the Islamic marketing mix in the context of Islamic bank strategy in Indonesia. The main problem studied is how Islamic banks can develop effective marketing strategies to increase market share in the midst of increasingly fierce competition. This research is motivated by the need to understand marketing approaches that are in accordance with sharia principles and the characteristics of Muslim customers. The method used in this research is qualitative, with data collection techniques through in-depth interviews and document analysis related to Islamic bank marketing strategies. The results showed that the Islamic marketing mix which includes product, price, place, and promotion plays an important role in attracting customers and increasing their satisfaction. The conclusion of this study confirms that the implementation of a marketing mix in accordance with Islamic values can be an effective strategy for Islamic banks to win the competition and expand market share.